Asymptomatic group B streptococcal bacteriuria among pregnant women in Saudi Arabia - Ahmad, S. (British journal of biomedical science, 2015)
This study aims to determine the asymptomatic bacteriuria in pregnancy due to GBS and its antimicrobial sensitivity pattern for planning strategy for the management of these cases and also to determine the relationship between asymptomatic bacteriuria and pyuria. A total of 3863 consecutive urine specimens were collected from 3863 pregnant women with asymptomatic bacteriuria attending the obstetrics and gynaecology department of our hospital over a period of two years. Specimens were processed using standard microbiological procedures. All the subjects were evaluated for bacteriuria. The prevalence of asymptomatic bacteriuria due to group B streptococci (GBS) was 82/3863 (2.1%) among pregnant women in Saudi Arabia. Among these, 69/82 patients (84.2%) had clinical and microbiological features consistent with cystitis, versus 13/82 (15.8%) for pyelonephritis. About 51.2% (42/82) of the patients who had urine analysis performed had positive results based on positive urinary leucocyte esterase and pyuria. Disc-diffusion analysis of all 82 GBS isolates showed that they were highly susceptible to Augmentin and linezolid. Screening for bacteriuria in pregnancy and proper treatment must be considered as an essential part of antenatal care in this community. To prevent asymptomatic bacteriuria complications, all pregnant women should be screened at the first antenatal visit. A negative test for pyuria is not a reliable indicator of the absence of asymptomatic bacteriuria in pregnant women. Further, ongoing surveillance and evaluation of outcomes in pregnancies complicated by GBS bacteriuria is required to optimise maternal and newborn care.